1998
DOI: 10.1017/s0025315400041643
|View full text |Cite
|
Sign up to set email alerts
|

Distributions, Size Compositions and Diets of Two Abundant Benthic Ambush-Feeding Teleosts in Coastal Waters of South-Western Australia

Abstract: The scorpaenid Maxillicosta scabriceps (Teleostei) and the platycephalid Platycephalus longispinis (Teleostei) were trawled seasonally for a year from shallow (5-15 m) and deeper (20-35 m) waters in four distantly-located regions of the inner continental shelf of south-western Australia. The former species was more abundant in southern regions, which is consistent with its temperate distribution, while the latter species was more abundant in deep than shallow waters. Unlike M. scabriceps, P. longispinis with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 42 publications
(102 reference statements)
0
33
1
Order By: Relevance
“…Ontogenetic dietary shifts were demonstrated for the species in western Mediterranean waters (Sartor & De Ranieri, 1996; Morte et al , 1999). These differences might reflect a combination of increasing mouth size and an improved ability to handle prey and to swim faster (Gerking, 1994; Platell & Potter, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Ontogenetic dietary shifts were demonstrated for the species in western Mediterranean waters (Sartor & De Ranieri, 1996; Morte et al , 1999). These differences might reflect a combination of increasing mouth size and an improved ability to handle prey and to swim faster (Gerking, 1994; Platell & Potter, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors (e.g. Braber and de Groot, 1973;Gerking, Platell and Potter, 1998) have shown that an increase in size of fish is associated with an increase in the consumption of larger prey, reflecting in some species a combination between increase in mouth size and improved ability to handle prey and to swim faster. This is in agreement with the optimum foraging theory (Gerking, 1994), according to which larger predators consume larger prey to maximise the energy gain relative to capture effort.…”
Section: Dietmentioning
confidence: 99%
“…Given the perception that soft sediment fishes are unlikely to show site attachment [7], and observations that blue-spotted flathead can be strong active swimmers (Fetterplace personal observation from baited underwater video; see data and materials section), it is particularly interesting that the majority of tagged fish in our study showed such strong site attachment. The ability of blue-spotted flathead to target many types of prey [19] coupled with the expected ambush predation by flathead species in general [20] could explain why blue-spotted flathead generally utilise relatively small areas over a day. Why some individuals continue to show this compact space use over periods of 60 days and others move away is not clear.…”
Section: Discussionmentioning
confidence: 99%